Synthesis of uniformly dispersed silica/graphene oxide composite hydrogel using acid/base combinatorial catalysts system. (March 2021) - Oh, Byeolnim; Oh, Jun-Sung; Lee, Eun-Jung; Han, Cheol-Min
Abstract: This study involved the preparation of a sol–gel-based silica hydrogel, which incorporates uniformly dispersed graphene oxide (GO), using an acid/base combinatorial catalyst system. The gelation time of the silica hydrogel was dramatically reduced by adding the combinatorial catalyst instead of using a single catalyst system. Raman mapping confirmed that the combinatorial catalyst system considerably improved the uniformity of GO dispersion in the silica matrix. The silica/GO composite hydrogel demonstrated a very wide range of elastic moduli, compressive strength, and strain at fracture, indicating that this composite hydrogel system could potentially be used as a platform for stem cell culture or as a stretchable gel.